Dermatological Manifestations of Wilson’s Disease: Two Cases - Alam, Rubaiyat; Karim, ASM Bazlul; Rukunuzzaman, Md; Hossen, Kamal; Thakur, Shashi Bhushan; Uddin, Mohammad Moin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Wilson's disease, an autosomal recessive disorder of copper metabolism, most commonly presents either with hepatic or neurological features. But it may sometimes have certain atypical presentations which may lead to diagnostic difficulties. We report here two cases who were diagnosed as Wilson's disease with prominent skin lesions over both lower extremities. These cases are reported here as it is rare and to highlight the fact that early recognition of the skin lesions may play a role in the diagnosis of Wilson's disease. The need to highlight the importance of skin lesion as a pointer to the early diagnosis of Wilson's disease because specific treatment can prevent further liver injury and neurological complications in most cases. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 59-62